2003
DOI: 10.1139/p02-137
|View full text |Cite
|
Sign up to set email alerts
|

Compressive strength of iceberg ice

Abstract: The uniaxial compressive strength of iceberg ice was determined over a wide range of strain rates from 10–8 to 10+1 s–1 at –10°C. It was found that for strain rates less than 10–4 s–1, strength increased in a power-law manner with strain rate. Above 10–4 s–1, the strength was essentially constant at 4 MPa, dropping slightly between 10–3 and 10–1 s–1, before rising again to a value of about 10 MPa at 10+1 s–1. Thin sections of the ice revealed a small grain size of about 3.5 mm and elongated air bubbles with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 6 publications
1
17
0
Order By: Relevance
“…Data with solid mark are test results at about near melting point temperature of −2.0 to 0 °C, and data with hollow mark are test results at about −10 °C. It is found that dependence of strain-rate and compressive strength under moderate strain rates found in pre-sent study is consistent with studies of Shazly et al (2009), Meglis et al (1998 and Jones et al (1997;2003). While study of Combescure et al (2011) showed the strength is independent of strain-rate over 10 −2 to 50 s −1 strain-rate range.…”
Section: Strain-rate Effect On Compressive Strength Of Natural Icesupporting
confidence: 89%
See 1 more Smart Citation
“…Data with solid mark are test results at about near melting point temperature of −2.0 to 0 °C, and data with hollow mark are test results at about −10 °C. It is found that dependence of strain-rate and compressive strength under moderate strain rates found in pre-sent study is consistent with studies of Shazly et al (2009), Meglis et al (1998 and Jones et al (1997;2003). While study of Combescure et al (2011) showed the strength is independent of strain-rate over 10 −2 to 50 s −1 strain-rate range.…”
Section: Strain-rate Effect On Compressive Strength Of Natural Icesupporting
confidence: 89%
“…The results of Jones et al (2003) are uniaxial compressive strength of iceberg ice over a very wide strainrate range (10 −8 to 10 1 s…”
Section: Strain-rate Effect On Compressive Strength Of Natural Icementioning
confidence: 99%
“…Specific scenario in collision of double hull tanker by level ice was conducted by Cao et al [59] that concluded in side penetration by level ice, inner hull still in safe condition. Indication of improvement in material properties under polar condition is widely open as previously was initiated by Daley [60] for empirical formula in calculating ice characteristic, Jones et al [61] and Kim [62] in ice modelling, Min et al [63] for mechanical properties for steel in extreme condition, and structure-ice interaction by Gagnon & Derradji-Aouat [64] which was later implemented in compressive ice scenario by Bae et al [65]. These references indicate that proper modelling should be performed not only on the ship but also striking object, as ice in collision and sea bottom in grounding.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for choosing these temperatures was to compare the crushing test in a warmer and cooler environment. Both temperatures are practical for an ice-covered region, as described by Jones et al (2003), iceberg temperatures vary from 0°C to -10°C from the surface of the ice to a depth of 1-2 meters.…”
Section: Test Plan Designmentioning
confidence: 99%
“…Figure 3.12 shows an ice cone with a 30° cone angle (Dillenburg, 2012). Figure 3.12: Ice sample of 30° cone angle (Dillenburg, 2012) In the current work, the shaping was stopped when the top of the ice samples reached After shaping, the ice specimens were covered and stored in the cold room for at least twenty-four (24) hours to adjust it to the desired temperature (Jones et al, 2003).…”
Section: Ice Specimen Shapingmentioning
confidence: 99%